Ornament as a specific sign of ethnic groups non-verbal communication (Journal of Philosophy Culture and Political Science, 2018)
Ornament is considered as a semiotic sign, which has meaning and acts as a type of nonverbal communication. Passion for the question of «language and culture» is dictated by the modernization processes increasing in the modern era the problem of the dialogue of cultures, intercultural communication. Nodal consignee of modernization is the probability of ethnic culture and symbolism copulation. According to this traditional ornament is considered in the light of the ethnic groups non-verbal communication specific sign, describes the symbolic meaning of ornament, which recreates the worldview and mentality of a particular ethnic group. The paper pays special attention to the multiplicity of signs and semiotic meaning of the ornaments, using a semiotic method of classifying them according to various criteria. Also the typology of the ornaments from different time periods provides an opportunity to discover their mutual permeability and dialogism. Ornament is revealed as a sign of ethnic culture, showing about culture features of particular ethnic group and thus acts as an interesting aspect of nonverbal communication.Key words: verbal and non-verbal means of communication, traditional patterns, classification, meaning, ethnic culture, the metalanguage of mankind.